IMPLEMENTASI KURIKULUM MERDEKA DI MI ISLAM PURWOKERTO SRENGAT BLITAR TAHUN AJARAN 2023/2024 - Saputra, Angga Nuraufa Zamzami; Muhammad Muslih; Wahyu Lailatul Baridah (Comprehensive Journal of Islamic Studies, 2023)
The curriculum in Indonesia continues to undergo improvements. Currently, the Independent Curriculum is the newest curriculum initiated by the Ministry of Education and Culture. Even though this curriculum is not yet mandatory in all units, the Independent Curriculum is a hot topic being discussed in the world of education. This article discusses the implementation of the Merdeka Curriculum in one of the institutions that is not a driving school, namely MI Islam Purwokerto Srengat Blitar. The aim is to measure the extent of implementation of the Independent Curriculum in the unit. This research uses a qualitative method with a descriptive presentation of the reduction results from data obtained through observation, interviews and documentation. The results of this research are: 1) MI Islam Purwokerto uses teaching modules that are in accordance with the Merdeka Curriculum; 2) MI Islam Purwokerto increases the time available for practical activities, out-of-class learning and project-based learning in order to develop student character, competence and creativity; 3) MI Islam Purwoketo has implemented learning in 3 types of activities, namely intracurricular, extracurricular and co-curricular.